Association of a serotonin transporter gene polymorphism (5-HTTLPR) and stressful life events with postpartum depressive symptoms: a population-based study. (March 2013) - Tavares Pinheiro, Ricardo; Monteiro da Cunha Coelho, Fábio; Azevedo da Silva, Ricardo; Amaral Tavares Pinheiro, Karen; Pierre Oses, Jean; de Ávila Quevedo, Luciana; Dias de Mattos Souza, Luciano; Jansen, Karen; Maria Zimmermann Peruzatto, Josi; Gus Manfro, Gisele; Giovenardi, Márcia; Almeida, Silvana; et al.
Abstract: We conducted a cross-sectional study nested within a cohort study with 276 postpartum women to evaluate the role of a serotonin transporter gene polymorphism (5-HTTLPR) and the stressful life events (SLE) on the risk of postpartum depression (PPD) symptoms in a community sample. Participants were assessed between 45 and 90 days after delivery with the Edinburgh Postnatal Depression Scale (EPDS) and the Mini International Neuropsychiatric Interview (MINI). Data regarding socio-demographic variables, alcohol consumption, tobacco smoking and SLE occurring during pregnancy, were also collected. In the adjusted analysis, the women carrying the long (L) allele (LL) who experienced SLE showed higher prevalence ratios (PR) for PPD symptoms (EPDS ≥13) than those with two copies of the short (S) allele (SL) (PR = 9.91; 95% confidence interval: 1.70–57.87). In contrast, a trend of association was found between prior history of major depressive disorder (MDD) and the S allele carrier status ( p = 0.07). No association was found between the formal diagnosis of current MDD and the 5-HTTLPR genotypes. In line with previous reports, we find in this sample that the L allele carrier status was associated with a heighten risk of depressive symptoms in postpartum when SLE were experienced during pregnancy.